2008
DOI: 10.1111/j.1365-2702.2008.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between work empowerment and work stress perceived by nurses at long‐term care facilities in Taipei city

Abstract: The managers of the facilities should provide available resources for nurses to accomplish work and to involve nurses in the development goals of the facilities to enhance their influence in the making of important changes within the organisation to decrease their work stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 19 publications
3
46
0
1
Order By: Relevance
“…These results are in line with the hypothesized models, which suggest that access to structural empowerment (Kanter, 1993) has positive effects on managers' behaviors (Spreitzer, 1995), leading to lower self-rated stress symptoms and higher self-rated leadership-management performance. Previous cross-sectional studies and two longitudinal studies have shown that structural and psychological empowerment has a positive effect on nurses' job satisfaction (Laschinger et al, 2004;Li, Kuo, Huang, Lo, & Wang, 2013) and burnout rates (Laschinger et al, 2003), which leads to decreased stress for nurses (Li et al, 2008). Furthermore, a leadership program based on structural and psychological empowerment was reported to increase managers' self-confidence and to positively affect their leadership styles (Macphee et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results are in line with the hypothesized models, which suggest that access to structural empowerment (Kanter, 1993) has positive effects on managers' behaviors (Spreitzer, 1995), leading to lower self-rated stress symptoms and higher self-rated leadership-management performance. Previous cross-sectional studies and two longitudinal studies have shown that structural and psychological empowerment has a positive effect on nurses' job satisfaction (Laschinger et al, 2004;Li, Kuo, Huang, Lo, & Wang, 2013) and burnout rates (Laschinger et al, 2003), which leads to decreased stress for nurses (Li et al, 2008). Furthermore, a leadership program based on structural and psychological empowerment was reported to increase managers' self-confidence and to positively affect their leadership styles (Macphee et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…However, only two Canadian studies have been found using a longitudinal approach to link structural and psychological empowerment to nurses' job satisfaction (Laschinger, Finegan, Shamian, & Wilk, 2004) and burnout rates (Laschinger, Finegan, Shamian, & Wilk, 2003), and none in the care of older adults. Cross-sectional studies among nurses have found that structural and psychological empowerment was negatively associated with work stress (Li, Chen, & Kuo, 2008) and burnout (Meng et al, 2015(Meng et al, , 2016. However, most studies investigate these relationships among nurses (Guo et al, 2015), rather than from the perspective of managers.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Using a convenience sampling strategy, the RNs having more than 2 months of working experience in their current geriatric hospitals were invited to this study. Two-month working experience was determined based on small bed sizes ranging from 99 to 269, 1-month job orientation period for new nurses of the participating geriatric hospitals and a literature review regarding perceived empowerment of nurses [25].…”
Section: Setting and Samplementioning
confidence: 99%
“…1 Access to resources refers to the ability of the individual to access the materials, money, supplies, time, and equipment required to accomplish organizational goals. 11,12 Access to information technical knowledge, and expertise required to perform one's job. 13,14 Access to Opportunity refers to professional growth and development opportunities to build on the knowledge and skills required for the job.…”
Section: Structural Empowermentmentioning
confidence: 99%